The Dynamics of Money Demand and Prices. (IMF Working Papers; Working Paper, 1990)
The paper evaluates whether a monetary aggregate can serve as a useful predictor of inflation, using recent developments in the principle of cointegrated variables. M2 but not M1 is cointegrated with relevant price, transactions, and rate of return variables. However, deviations of M2 from its long-run equilibrium value do not significantly enhance inflation forecasts based on conventional output-gap models, a result that stands in contrast to the Federal Reserve's P* relationship. Nevertheless, changes in M2 do contain information about future inflation, consistent with the view that the demand for money reflects the forward-looking behavior of private agents.